Extension and advisory services: Supporting communities before, during, and after crises - Grove, Benjamin; Archibald, Thomas; Davis, Kristin E. (Virginia Polytechnic Institute and State University, 2020)
Extension and Advisory Services (EAS) providers are important partners for communities to prepare for, respond to, and recover from shocks such as natural disasters and human, plant, and animal disease and pest outbreaks. EAS providers work long-term in communities to equip people with knowledge, skills, and technical resources to improve their livelihoods. EAS are provided by various actors including governments, nongovernmental organizations, private sector entities, higher education institutions, and other organizations. EAS often serve in bridging roles connecting resources from numerous actors operating in communities and are valuable conduits of information during shocks. EAS are seen as key partners in helping communities rebuild and strengthen food systems after the initial shock, given their long-term work horizons. There are numerous examples of EAS responding to crises around the world, such as HIV/AIDS, Ebola, Avian Influenza, malaria, and, more recently during the current COVID-19 pandemic. During COVID-19, EAS have undertaken an unprecedented shift to virtual and distanced programming as daily life has been disrupted through restrictions on movement and gatherings. EAS agents have been challenged to modify program delivery and remain effective in serving their clientele while navigating this new landscape. In this essay we explore examples of EAS supporting communities before, during, and after crises, and discuss implications for future EAS work, including considerations of lessons learned during the COVID-19 pandemic response.